Mekanisme Corporate Governance, Size, Dan LikuiditasPerusahaan Terhadap Pemicu Peringkat Obligasi(Studi Empiris Pada Perusahaan Manufaktur YangTerdaftar Di Bei Tahun 2011-2014). - Helmi, Adib Faizal; , Dr. Fatchan Achyani, S.E.,M.Si (2017)
The aimed of this study is to know the relationship of coorporategovernance mechanism, size, licuidity of company to trigger of bond rating. Corporate governance mechanism in the proxy with the managerial ownership, institutional ownership, amount of the broad of commissioner, proportion of independent commissioner, and audit commite. Size in proxy with log natural total asset, and licudity in the proxy with the current ratio. This study usied data from 32 Manufacture Company listed on BEI since 2011-2014. Collecting data used purposive sampling metoth and analized by double linear regretion, classical assumption test, F test and T test. The results show that the managerial ownership, institutional ownership, size, and licuidity have influential on earning bond ratings.The amount of broad commissioner, Proportion of independent commisioner, audit comitee has no effect on bond rating.